Impact of pesticide regulations on mortality from suicide by pesticide in China: an interrupted time series analysis - Yan, Yongfu; Jiang, Yingying; Liu, Rong; Eddleston, Michael; Tao, Chuanjiang; Page, Andrew; Wang, Lijun; Feng, Guoshuang; Liu, Shiwei (Frontiers in Psychiatry, 2023)
Background: Pesticide bans and regulatory restrictions have been shown to be effective strategies for preventing suicide in several countries. Suicide and suicide by pesticide have decreased significantly in China over the past two decades. However, does whether the successive reduction was associated with pesticide regulations is unknown.: The monthly data on suicide and suicide by pesticide data from 2006 to 2018 were obtained from China's Disease Surveillance Points (DSPs) system. Information on China's pesticide regulations since 1970 was reviewed from Pesticide Action Network International (PAN International), Joint Meeting on Pesticide Management Highly Hazardous Pesticides (JMPM HHP) lists, website of the Ministry of Agriculture of China, Pesticide Information Network of China and Wan Fang database. Change point detection and policy analysis were combined to identify the time of any trend change breakpoint of suicide and suicide by pesticide.Interrupted time series analysis was used to investigate the pre-and post-breakpoints trend of monthly standardized rates in suicide and suicide by pesticide.The standardized suicide by pesticide rate decreased by 60.5% from 6.50 in 2006 to 2.56 per 100 000 in 2018. Larger declines were evident among people in urban areas (67.3%), females (63.5%), and aged 15-44 years (68.1%). The effect of policies was more pronounced banning in banning highly hazardous organophosphorus pesticides (HHOP) (Rate ratio (RR)=0.993, 95% CI 0.991 to 0.994) in December 2008 and stopping domestic sales and use of paraquat aqueous solution (RR=0.992, 95% CI 0.990 to 0.994) in July 2016 were more pronounced than regulating the paraquat-related products (RR=1.003, 95% CI 1.002 to 1.004) in April 2012.Declines in suicide by pesticide in China occurred contemporaneously with regulatory bans and restrictions on several pesticides implemented, particularly in urban areas, among females, and the age relative low profile. Indicating These findings indicate the potential influence of these bans on trends in suicide by pesticides.